ANALYSIS OF INVENTORY PLANNING FOR BRICK RAW MATERIALS USING THE MATERIAL REQUITMENT PLANNING (MRP) METHOD - Aisyah Siregar (Bajang Institute, 2022)
Material Requirement Planning (MRP) is a method used to control the availability of raw material planning for a product. MRP is a better inventory planning and scheduling technique for a unit of product produced. Problems at PT. Maju Jaya Prima Batu Bata. that has been implemented and researched by the author is about the availability of planning for raw materials for brick products, so that it is successful and on time as expected and in order to fulfill the ever-changing demand in each period. For this reason, proper planning is needed for the planning needs of red brick raw material inventory to run effectively and efficiently. Planning material requirements using the MRP method in this paper uses the lot sizing method, where the lot sizing methods used are Lot-for-lot, Economic Order Quantity (EOQ) and Period Order Quantity (POQ), as well as using Moving Average and Simple forecasting. Average to find out the need for raw materials in the future. Based on the results of the smallest MSE calculation, the method chosen is the Moving Average with a value of 72,211,414. Based on the results of the MRP calculation with the lot sizing technique, namely POQ, resulting in a total cost of 1,939,788 orders for the minimum raw material, POQ is used as a solution for controlling raw material inventory at PT. Maju Jaya Prima Batu Bata.